Sorption of Triclosan onto Tyre Crumb Rubber - J. López-Morales; O. Perales-Pérez; F. Román-Velázquez (Adsorption Science & Technology)
The effectiveness of using tyre crumb rubber (TCR) as an adsorbent for the removal of triclosan (TCS) from aqueous solutions was evaluated as a function of pH through controlled batch experiments. Carbon black (CB) and styrene–butadiene polymer (SBP), which are the main components in TCR, were individually evaluated and their contribution in the sorption process was assessed. At pH 3, the maximum rate of adsorption of TCS onto TCR, CB and SBP was 89, 95 and 92%, respectively. The Freundlich model provided the best fit for the experimental data obtained, as indicated by the mean relative percent deviation modulus (P). Our study results indicate that the removal of TCS using SBP follows an absorption process. Maximum desorption rate of TCS from TCR was approximately 89%. Results of sorption/desorption experiments clearly indicated the viability of TCR to be reused without any significant loss in its sorption/desorption capacity.